2007
DOI: 10.1159/000106575
|View full text |Cite
|
Sign up to set email alerts
|

S-100B and FDG-PET/CT in Therapy Response Assessment of Melanoma Patients

Abstract: Objective: To compare the value of the tumor marker S-100B protein and fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) in patients treated for melanoma metastases. Methods: In 41 patients with proven melanoma metastases, S-100B measurements and FDG-PET/CT were performed before and after therapy. The change of S-100B levels (ΔS-100B) was assessed. In all patients, therapy response was assessed with PET/CT using visual criteria and change of maximal standard uptake value (ΔSUV Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 43 publications
2
17
0
1
Order By: Relevance
“…In the present study 36% patients failed to show elevated S-100B values despite the presence of proven distant metastases. This is in keeping with a previous study where 15 of 41 patients (37%) showed a false-negative S-100B before therapy of metastases (16).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study 36% patients failed to show elevated S-100B values despite the presence of proven distant metastases. This is in keeping with a previous study where 15 of 41 patients (37%) showed a false-negative S-100B before therapy of metastases (16).…”
Section: Discussionsupporting
confidence: 93%
“…Current data regarding therapy assessment of melanoma patients with PET or PET/CT is limited to case reports showing the effect of limb perfusion therapy and one study comparing change of PET/CT findings to change of S-100B values in a mixed population of stage III and stage IV melanoma patients during different therapies (surgery or chemotherapy) (16,17). To our knowledge, this is the first study comparing S-100B, FDG-PET/CT and CT alone for therapy response assessment by using outcome data.…”
Section: Fdg-pet/ct Is Increasingly Used For Therapy Assessment Of DImentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few reports on the use of 18 F-FDG PET for the assessment of early prediction of response to therapy and outcome in patients with other malignancies, such as ovarian cancer (72,73), uterine cancer (73), head and neck squamous cell carcinoma (74,75), sarcoma (76), mesothelioma (77), and melanoma (78).…”
Section: Miscellaneousmentioning
confidence: 99%
“…Coregistred 18 F-FDG-PET/CT has been available for a few years and provides such anatometabolic datasets in a single examination. 18 F-FDG-PET/CT has been found to be superior to CT alone and PET alone in staging and evaluation of therapy response in several oncological diseases including malignant melanoma [11][12][13]. 18 F-FDG-PET/CT as a functional and anatomical imaging method provides additional information for surgical therapy planning.…”
Section: F-fdg-pet/ctmentioning
confidence: 99%